Luminescence and biological properties of Ag doped Dy:(ZnO–Li2O–Na2O–P2O5) glass. (2nd April 2020) - Pathak, Trilok K.; Viljoen, Bennie; Swart, Hendrik C.; Kroon, R. Edward
ABSTRACT: The melt quench technique was used to prepare phosphate-based glasses composed of ZnO–Li2 O–Na2 O–P2 O5 which were activated with luminescent Dy 3+ ions and doped with various concentrations of Ag. X-ray diffraction was used to confirm the formation of amorphous glass material. The glasses were characterised by density measurements, absorption spectroscopy and by photoluminescence excitation and emission scans. Four emission bands at 482 nm (blue), 573 nm (yellow), 663 nm (red) and 752 nm (red) were recorded, corresponding to transitions of Dy 3+ ions. Antibacterial tests were made against Escherichia coli, Staphylococcus aureus and Listeria monocytogenes, while antifungal tests were performed with the yeasts Candida albicans and Cryptococcus neoformans . Doping with a low concentration of Ag enhanced the luminescent and antimicrobial properties, although higher doping levels led to the formation of metallic Ag nanoparticles and a decrease in these useful properties.